Analisis Pemahaman Konsep Matematika Kelas VII SMP Negeri 5 Cibitung Pada Materi Bilangan Rasional - Zanuar Renaldie (LPPM Politeknik Pratama, 2023)
The purpose of this study was to describe the understanding of mathematical concepts of seventh grade students of SMP Negeri 5 Cibitung on rational number material. The method used in this research is descriptive qualitative method. This research was conducted at SMP Negeri 5 Cibitung involving 20 students as research subjects. Data collection using a description test related to rational number material. The results of the research obtained by the ability to understand mathematical concepts of seventh grade students of SMP Negeri 5 Cibitung are low. This can be proven by based on research data. The percentage frequency distribution of students' overall mathematical concept understanding ability is obtained by a total score with very low criteria as many as 1 student, a total score with low criteria as many as 11 students, a total score with sufficient criteria as many as 2 students and a total score with good criteria as many as 3 students and a total score with very good criteria as many as 3 students. It can be concluded that the success of learning has not been achieved because concept understanding has not met the standards.